2021
DOI: 10.15549/jeecar.v8i4.840
|View full text |Cite
|
Sign up to set email alerts
|

Effective strategies to manage the teacher intellectual work productivity in distance learning

Abstract: The article aims to empirically determine the effective strategies to manage intellectual work (IW) productivity (IWP) in distance learning (DL), for example, university teachers in Georgia. Based on the expert assessment methods, determining indicators for assessing the level of Teacher Intellectual Work Productivity (TIWP) of three large universities in Georgia and its current level was analyzed using the method of integral assessment.  Using the ANOVA method, determined the main factors influencing the TIWP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Numerous studies on academic personnel are related to challenges in career management. The focuses of these studies were conflict situations in educational institutions, the effect of stress on academic performance, work-life balance, the regulation of the remuneration system, discriminatory decisions, supervisor support concerns, and other topics (Kharadze et al, 2021;Gagnidze & Vesperi, 2021;Ahmady et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Numerous studies on academic personnel are related to challenges in career management. The focuses of these studies were conflict situations in educational institutions, the effect of stress on academic performance, work-life balance, the regulation of the remuneration system, discriminatory decisions, supervisor support concerns, and other topics (Kharadze et al, 2021;Gagnidze & Vesperi, 2021;Ahmady et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This was due to the fact that within entrepreneurial universities, there is space for an effective dialogue between various educational, scientific, business and public authorities (Gogorishvili and Zarandia, 2021;Seturidze and Topuria, 2021; Vesperi and Gagnidze, 2021b). Moreover, these authorities can quickly commercialise research, introduce the results to the market, and retrain fully qualified specialists (Guerrero et al, 2016;Kharadze et al, 2021;Lekashvili and Bitsadze, 2021;Papachashvili et al, 2021;Sciarelli et al, 2022;Sobolieva et al, 2021). Due to their relevance, below a few key factors have been identified that contribute to the efficient functioning of entrepreneurial universities, namely: the creation of an "entrepreneurial environment, entrepreneurial staff as well as entrepreneurial teaching and learning; a strong entrepreneurial vision and the presence of leaders; the need for an environment of awareness to support spin-off creation; identifying factors that determine continuous organisational success" (Dominici and Gagnidze, 2021, p. 24).…”
Section: What Characteristics Will Enable the Cluster To Overcome The...mentioning
confidence: 99%
“…Moreover, these authorities can quickly commercialise research, introduce the results to the market, and retrain fully qualified specialists (Guerrero et al. , 2016; Kharadze et al. , 2021; Lekashvili and Bitsadze, 2021; Papachashvili et al., 2021; Sciarelli et al.…”
Section: What Characteristics Will Enable the Cluster To Overcome The...mentioning
confidence: 99%
“…Furthermore, it typically has a detrimental effect on their health. One of the primary challenges for retiring professors is the balance between their job and personal lives [15,16,17].…”
Section: Literature Reviewmentioning
confidence: 99%